BAYESIAN STATISTICAL FUSION RELIABILITY EVALUATION MODEL OF MULTI-SOURCE HETEROGENEOUS DATA - TANG Li; TANG JiaYin; CHENG ShiJuan (Jixie qiangdu)
In order to solve the reliability evaluation of small samples for the high reliability, long-life products and to improve the accuracy of reliability evaluation, the Bayesian reliability evaluation model of multiple information source data fusion was carried out. First, a set of data as the initial prior information of another information source in this model was selected, by using the posterior density according to Bayesian estimation. Then, it as the prior distribution of the next information source was used. Through iteration, the joint posterior density and reliability index data of multi-source heterogeneous data are obtained, and the corresponding reliability analysis is completed. Finally, a simulation example verifies the rationality and effectiveness of the model.